An Approach to Measuring Dispersed Families with a Particular Focus on Children 'Left Behind' by Migrant Parents: Findings from Rural South Africa. Issue 4 (8th January 2014) - Bennett, Rachel; Hosegood, Victoria; Newell, Marie‐Louise; McGrath, Nuala
Abstract There is growing policy and academic interest in the conditions, experiences, and well‐being of migrant families stretched across origin and destination households. In South Africa, the dispersal of children and migrant parents across multiple households is a commonplace childhood experience. However, in common with the broader international context, quantitative analyses of the social and residential connections between children and migrant parents in South Africa have been limited by the lack of available data that document family arrangements from the perspective of more than one household. This paper describes a new data collection effort in the origin and destination households of migrants from rural KwaZulu‐Natal and explains the methodology for using this data to examine multiple household contexts for children and parents. In order to illustrate the contribution that this form of data collection effort could make to family migration studies, the paper also presents results on the living arrangements of children 'left behind' by migrant parents; a potentially vulnerable group whose arrangements are challenging to examine with existing data sources. The empirical results show the majority (75%) of left behind children have previously migrated and a significant proportion of migrants' children (25%) were not living in their parent's origin or destination household. The findings highlight the need for careful measurement of the circumstances of left behind children and demonstrate the contribution of linked data for providing insights into the residential arrangements of migrants' children. © 2014 The Authors. Population, Space and Place published by John Wiley & Sons Ltd